And How Would That Make You Feel? How People Expect Nudges to Influence Their Sense of Autonomy - Wachner, Jonas; Adriaanse, Marieke A.; De Ridder, Denise T. D. (Frontiers in Psychology, 2020)
Objective: While nudges are increasingly utilized in public policy settings, their potential threat to autonomous choice is the topic of heated debate. Regardless of the actual effects of nudges on autonomy, the mere perception of nudges as autonomy threatening by the general public or policy makers could already negatively influence nudge acceptability. The present online studies examined how people expect (different) nudges to affect their autonomy. Method: In the first study (N = 455), participants were presented with a hypothetical choice that employed either a default nudge, direct persuasion, or no persuasion, to steer to the desired choice. The presented influence technique was explained before participants reported their expected autonomy, as well as their expected choice satisfaction. Study 2 (N = 601) involved a replication of Study 1 with an additional social norm nudge condition. In Study 3 (N = 750), the explanation of how choice had been influenced was omitted. Results: While participants expected the default nudge to violate autonomy (Study 1), they had no such expectations for social norm nudges (Study 2). Omitting the explanation that most people are unaware of nudges influencing their choice, reduced the negative impact of nudges on expected autonomy (Study 3). Conclusion: Effects of nudges on expectations of autonomy differ by type of nudge. Negative expectations are primarily driven by the explanation that decision makers are often unaware of nudges.